Microbiological Assessment and Detection of Adenovirus in Sachet Water Sold In Abeokuta, Nigeria (2021)
Microbiological safety of sachet water remains a public health problem in Nigeria. This study was aimed at investigating some packaged sachet water sold in Abeokuta, South-West Nigeria for the microbiological safety including some of the enteric viruses on contaminant candidate list. Sachet water samples from five different producers were obtained over three month’s period. Bacterial and fungal analyses were conducted with standard culture method. Targeted protozoans were investigated by microscopic examination of sediments obtained after centrifugation. Nested and semi-nested polymerase chain reaction (PCR) techniques targeting specific genes in adenovirus, norovirus and rotavirus were used for viral analyses. Results were presented in presence-absence score. Contingency table was used to establish relationship between viruses, Escherichia coli and protozoans. Out of a total twenty pooled samples analysed, adenovirus had a prevalence rate of 10% across the study period, whereas rotavirus and norovirus were absent. Giardia cysts and Cryptosporidium oocysts were also absent. Escherichia coli was present in 40% of the brands. Other bacteria identified were Salmonella enterica serovar Typhi, Shigella dysentariae, and Pseudomonas aeruginosa. Aspergillus sp, Mucor and Rhizopus sp. were present in some samples collected. Adenovirus was detected by PCR in a pooled sample of sachet water thattested negative for Escherichia coli, Cryptosporidium oocysts and Giardia cysts. There is need for microbiological screening of sachet water periodically in order to enhance public health safety.